Evaluasi Pelaksanaan Prosedur Pelayanan Obat Pelengkap Oral Di Ruang Rawat IRNA B Perjan RS Dr. Cipto Mangunkusumo Jakarta - Harianto, Harianto; Lestari, Itet; B, Laswety (UI Scholars Hub, 2005)
A research had been performed in order to get general description of the service of an oral complementary drug in the nursing ward of IRNA B of Perjan RS Dr. Cipto Mangunkusumo and it evaluated the operation of the oral complementary drug service was, and also found out the correlation of the orderly medication instruction writing of the oral complementary drug, the orderly operation of the process of the oral complementary drug procurement, drug preservation, drug preparation, the hand-over the oral complementary drug to a patient, and Communication, Information and Education (CIE) in the nursing ward of IRNA B relation to the orderly operation of oral complementary drug service procedure. The research used the cross sectional method of survey which was descriptive and analytic in its nature. The research showed that 74,81% of the patients medication instruction writing in prescription did not fit the requirements in administration writing and medication information completely. 67,94% of the patients bought the prescription (76%-100%) form the drug store in RSCM, 42,75% of patients kept the 76%-100% of their drug in the pharmacy depot, 42,75% of patients prepared the 76%-100% of patient prepared the 76%-100% of their drug in unites of doses by the pharmacy depot. 64,12% of the patients were given their drug by nurses directly, and finished to swallow the drug according to its use direction, and there was none of the patients who got CIE service from a pharmacist. The operation of the oral complementary drug service in the nursing ward of IRNA B was evaluated as less appropriate to the procedure. It could be concluded that there is significant correlation between medication instruction writing, the orderly operation of the process of the oral complementary drug preservation, the drug preparation, the hand-over the oral complementary drug to a patient in the nursing ward of IRNA B with the orderly operation of oral complementary drug service procedure; and there is no correlation between the procurement of the oral complementary drug, the orderly operation of CIE in the nursing ward of IRNA B with the orderly operation of oral complementary drug service procedure.